A scoping review of empirical evidence on (digital) public services co-creation - A. Paula Rodriguez Müller; Cesar Casiano Flores; Valerie Albrecht; Trui Steen; Joep Crompvoets (Administrative Sciences, 2021)
The public sector is facing significant challenges regarding public services provision, including declination of users' trust and limited resources. An alternative approach to traditional public service provision with the potential to address these challenges is the co-creation of public services. Co-creation promises to foster innovative solutions to provide high-quality services that respond to users' needs. Considering this background, we aim at critically exploring public service co-creation via a scoping review, employing the PRISMA-ScR method. Our review focuses on 25 empirical studies out of 75 analyzed articles that examine the implementation of co-creation of (digital) public services and investigates how the empirical literature portrays the concept of public service co-creation. Our findings primarily suggest that co-creation can be implemented in a wide range of sectors and settings, to improve public services and to foster innovation, throughout the whole public service cycle, using a variety of digital, analog and hybrid co-creation tools and strategies. Yet, our review has also shown that there is still an implementation gap that needs to be bridged between knowing and doing in the context of public services co-creation in a digital setting.
Keywords: 350; digital transformation; co-creation; PRISMA; public services; scoping review